Faktor-Faktor yang Berhubungan dengan Kejadian Kanker Payudara pada Wanita Berusia di Bawah 40 Tahun - Carmenita Sinaga; Rani Lisa Indra; Bayu Saputra (Jurnal Siti Rufaidah, 2025)
Breast cancer is one of the types of cancer that has the highest incidence in women, with an increasing incidence at a young age. The aim of the study was to identify factors associated with the incidence of breast cancer in women under 40 years of age at RSUD Arifin Achmad Riau Province. This study used a case control design with a retrospective approach with a sample of 76. The sampling technique used was consecutive sampling. Data analysis was done with chi-square test. The results showed that the majority of respondents had high school education (55.3%) in the case group and (57.9%) in the control group, the average age of the case group was 36.05 and the control group was 33.58, the age of menarche (68.4%) in the case group and (28.9%) in the control group, breastfeeding history (47.4%) in the case group and (15.8) in the control group, hormonal contraception (13.2%) in the case group and (10.5%) in the control group, family history (44.7%) in the case group and (2.6%) in the control group. Bivariate analysis showed there was an association between menarche age factor (P = 0.001, OR = 5.318), breastfeeding history factor (P = 0.007, OR = 4.800), family history factor (P = 0.000, OR = 29.952) with the incidence of breast cancer. There was no association between hormonal contraceptive factors and the incidence of breast cancer (P=1.000, OR=0.776). The study concluded that the factors associated with breast cancer in women under 40 years old are age of menarche, breastfeeding history and family history. It is expected for women under 40 years old to routinely perform SADARI (breast self-examination) to prevent and detect early occurrence of breast cancer.